Application of Municipal Biowaste-Derived Products in Tomato Cultivation for Enhanced Fruit Quality Attributes and Nutritional Profile - Neofytou, Giannis; Chrysargyris, Antonios; Christodoulou, Marianna; Montoneri, Enzo; Koutinas, Michalis; Τζωρτζάκης, Νίκος Γ. (My University, 2025)
Enhancing plant nutrient use efficiency, yield, and quality without compromising sustainability remains a critical challenge in agriculture. Utilization of materials such as biowaste derivatives as alternatives to conventional agrochemicals (e.g., fertilizers, biostimulants) can be leveraged to optimize crop productivity and resilience while adhering to sustainable practices. A soluble bioproduct (BP), isolated from the hydrolysis of anaerobic digestates derived from organic residues of urban waste, was examined for its capacity to enhance tomato (Solanum lycopersicum) production and quality. Five basal fertilization treatments were applied: conventional (CF), conventional/organic (CF + OF), bioproduct at 150 kg ha-1 (BP), and conventional/BP at 150 and 300 kg ha-1 (CF + BP, CF + 2BP), without or with supplementary fertigation (SF). The experiment was arranged in a Randomized Complete Block Design. Intermediate plant growth under BP was comparable to CF, while their combination enhanced growth parameters. However, addition of BP to CF did not affect final plant growth, biomass, and yield compared to CF alone, though non-significant reductions of height (5.37%), leaf number (15.89%) and fresh weight (36.09%) were observed with BP alone. The same treatment reduced intermediate leaf macronutrients (N, K, Na), whereas this was ameliorated with CF + BP. The use of BP without fertigation enhanced final P content in leaves and roots. However, fruit P declined, reflecting delayed P availability and translocation. The use of BP induced plant stress responses, accompanied by stimulation of phenolic and antioxidant accumulation in leaves, with fruit exhibiting comparable increases only without fertigation. Fruit lycopene and total soluble solids were enhanced by CF + BP, with fertigation mediating differences. Combined CF and BP application promoted tomato fruit quality, without diminishing growth, while the performance of BP alone was improved with supplementary fertigation to maintain tomato growth, yield, and quality.
Keywords: tomato; bioproduct; fruit quality; municipal biowaste; plant growth